Penerapan Model Pembelajaran Problem Based Learning dengan Berbantuan Media Quizizz untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa SMP Swasta R.A Kartini Tebing Tinggi - Corry Patrisia Panggabean; Pardomuan N.J.M Sinambela (Journal on Education, 2023)
The purpose of this study was to improve students' mathematical problem-solving abilities by using the problem-based learning model with the help of Quizizz media in class VII of RA Kartini Tebing Tinggi Private Middle School, 2022/2023 academic year. The subjects in this study were 30 grade VII students of Private Middle School R.A Kartini Tebing Tinggi. Data collection techniques used by researchers are teacher and student observation sheets to test students' mathematical problem solving abilities and documentation. This research is a classroom action research which consists of 2 cycles, each cycle consisting of 2 meetings. Before carrying out the action, an initial ability test is first given and at the end of each cycle a student's problem-solving ability test is given. The test results of students' mathematical problem solving abilities increased from the initial test cycle I and cycle II. In the classical pre-test, 3 students (10%) passed and the average pre-test ability was 46.39 with a very low level of ability. In the first cycle test experienced an increase classically obtained 16 students (53.33%) completed and the average ability was obtained 69.44 with the level of ability in the sufficient category. Then in cycle II there was also an increase classically, 27 students (90%) completed and the average ability was obtained 86.67 with a very good level of ability. Thus it can be concluded that the application of the problem-based learning model with the help of Quizizz media can improve the mathematical problem-solving abilities of class VII students of Private Middle School R.A Kartini Tebing Tinggi.